Resistance to online learning in Zimbabwean secondary schools : the content and seasons - Vurayai, Simon (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
This study examined the content and reasons for the resistance to the implementation of online learning in secondary education in Zimbabwe in light of the lessons and experiences from the COVID-19 pandemic. The study employed a systematic literature review as its methodology that relied exclusively on secondary data. The Overcoming Resistance to Change (ORC) model was exploited as a desirable model for the review, findings, and recommendations. The study found that online learning as a pedagogical innovation is and has been resisted by stakeholders such as teachers, parents, and learners due to factors like poor communication, unpreparedness, education, and training. Other factors like isolation, costs, fear, vested interests, ingrained habits, and workload also compounded and increased the magnitude of resistance. The study recommended the need to overcome resistance to the implementation of online learning by proposing strategies such as education and communication, participation, negotiation, resource provision, and positive soft power
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (2) (2023)
Keywords: Innovation; Online Learning; Overcoming resistance to change; Resistance; Secondary education; Computer-assisted instruction; Technological innovations